CONSTRUCTION OF AN ALGORITHM OF CONDUCT OF SIGNS AND SYMPTOMS IN MALIGNANT NEOPLASTIC WOUNDS IN ADULTS (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To build an algorithm of conducts to control signs and symptoms of malignant neoplastic wounds in adults. Method: Methodological research, of an exploratory nature, for the construction-production of a clinical algorithm based on the scoping review. Results: A total of 107 studies was found in the databases, nine of which were included in this review. Four studies are randomized experimental studies, four are case studies and one is retrospective documentary observational study. Odor was the most addressed sign, followed by exudate, bleeding, infection, moisture-associated dermatitis, and pain. Conclusion: Gaps were observed, such as the need for more original and experimental studies, in addition to the lack of a specific descriptor for malignant neoplastic wound. However, it was possible to build an algorithm that offers conducts that are based on the literature for greater theoretical support and nursing safety in relation to cancer patients.